The Urgency of Debtor Protection from Misbruik Van Omstandigheden Carried Out by Creditors in the Implementation of Viat Parate Execution of Mortgage Collateral Objects - Amalia, Ayu Zahrina (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
.